Efektivitas Group Learning pada Pembelajaran Akidah Akhlak di Madrasah Ibtidaiyah - Farihatun Maulida, Salma; Syaifuddin, Mohammad (Indonesian Journal of Islamic Elementary Education, 2024)
The learning of Akidah Akhlak aims to develop creeds through understanding and appreciating the material as well as students’ practice of Islamic creeds so that they become muslims who believe and are devoted to Allah SWT. The aim of this research is to describe the effectiveness of implementing the group learning model in the Aqidah Akhlak subject in class V MI Ma’ahidul Huda Banjaran, Salem, Brebes Regency. This research uses a qualitative approach. Data collection was carried out by learning observations, interviews, and documentation. In analyzing the data, researchers used the Miles and Huberman model. The results of this research show that the use of the group learning model in learning moral beliefs is able to increase the effectiveness of learning and form students’ thinking intelligence, group organizing skills, and noble character towards others. Factors that support learning include teacher professionalism, support from the school principal, and good cooperation between teachers and students. Meanwhile, inhibiting factors are the teacher’s readiness in compiling certain material that is not well understood by students, students who are hyperactive so that it disturbs the concentration of other students, and students who are less active in learning.